2000
DOI: 10.1038/81343
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in caspase-9 or caspase-3 induces compensatory caspase activation

Abstract: Dysregulation of apoptosis contributes to the pathogenesis of many human diseases. As effectors of the apoptotic machinery, caspases are considered potential therapeutic targets. Using an established in vivo model of Fas-mediated apoptosis, we demonstrate here that elimination of certain caspases was compensated in vivo by the activation of other caspases. Hepatocyte apoptosis and mouse death induced by the Fas agonistic antibody Jo2 required proapoptotic Bcl-2 family member Bid and used a Bid-mediated mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
187
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(214 citation statements)
references
References 31 publications
23
187
3
1
Order By: Relevance
“…Recent cloning of DFF45/ICAD homologues raise the possibility that other DFF45/ DFF40 complexes exist which can be activated independently of caspase-3. Indeed, in support of this idea it has been demonstrated that, in the absence of caspase-3, hepatocyte cells induce compensatory caspase activation, such as caspase-6 (Zheng et al, 2000). This could also be the case for MCF-7 cells, as we have shown that…”
Section: Effect Of Staurosporine On Bcl-2 Bcl-x L Bak and Bax Proteisupporting
confidence: 74%
“…Recent cloning of DFF45/ICAD homologues raise the possibility that other DFF45/ DFF40 complexes exist which can be activated independently of caspase-3. Indeed, in support of this idea it has been demonstrated that, in the absence of caspase-3, hepatocyte cells induce compensatory caspase activation, such as caspase-6 (Zheng et al, 2000). This could also be the case for MCF-7 cells, as we have shown that…”
Section: Effect Of Staurosporine On Bcl-2 Bcl-x L Bak and Bax Proteisupporting
confidence: 74%
“…Similarly, analysis of genetic knockouts in mouse has revealed that Caspase-3 is essential in some cell types for apoptosis, but not in others, and that additional effector caspases can compensate for the loss of Caspase-3. 36 Interestingly, labeling of drICE 17 mutant embryos with cleaved caspase-3 (Caspase-3*) antibody produced a wildtype pattern. This is puzzling because the Caspase-3* pattern does not match the AO-and TUNEL patterns of drICE 17 mutants (Figure 3).…”
Section: Partial Redundancy Between Drice and Dcp-1mentioning
confidence: 99%
“…The timing of death varies among regions of the brain, from the early embryonic to the early postnatal periods. Mice lacking many of the other caspases, such as caspase 1, 2, 6, 11, or 12, do not have an obvious neuronal phenotype (Kuida et al, 1995;Bergeron et al, 1998;Namura et al, 1998;Wang et al, 1998;Zheng et al, 2000), but these caspases may play a role in regional pruning of neurons or in the plasticity of the nervous system.…”
Section: Developmental Death Pathways Inmentioning
confidence: 99%
“…This seems to be a significant problem with apoptotic genes, where phenotypic selection in developing embryos can severely alter normal expression patterns, as has been shown in caspase 2, 3, and 9 null mice (Zheng et al, 2000;Troy et al, 2001). Thus, removal of nerve growth factor (NGF) from cultured postnatal sympathetic neurons may induce parallel caspase pathways, and the dominant pathway depends on the relative concentrations of anti-and proapoptotic proteins (Troy et al, 2001).…”
Section: Developmental Death Pathways Inmentioning
confidence: 99%